The Role of Stakeholders in Strengthening the Mangrove Conservation in Banyuurip Mangrove Center, Gresik, East Java, Indonesia - Suhendri, Hendrik; Aditia, Dito; Gunawan, Cakti Indra (International Journal of Management and Business, 2024)
Mangroves are plant formations in coastal areas that have an important role. The area of mangroves in Indonesia continues to shrink, so it is necessary to strengthen the role of the stakeholders to support mangrove conservation. This research used a descriptive qualitative methods, with SWOT analysis. The results of the research show that 10 stakeholders play a role, namely the local community, the Banyuurip Village Government, the Banyuurip Mangrove Center Admin Team, the Non-Governmental Organization Volunteer Alliance for Saving Nature (Arupa), the private company, namely PGN Saka, Lecturers from Brawijaya University, Lecturers from Raden Rahmat University, Mass Media is Mongabay, public figure is the Chairman of the Banyuurip Mangrove and Environmental Conservation Group and the East Java Provincial Forestry Service. There are 11 strengths, 8 weaknesses, 12 opportunities and 4 threats, thus making the position of internal and external factors equally strong. The best strategy formulation is to strengthen the synergy between stakeholders through communication forums, synergize mangrove conservation programs and community socio-economic empowerment to strengthen human resource capacity, open space for aspirations to strengthen community interests and power in mangrove management policies and improve mangrove governance in Banyuurip Mangrove Center.